Environmental activism - Tabanli, Mustafa (New Jersey : Everest Production, 2008)
What is the current state of the environmental problem. Why this problem cannot be solved by science and education alone. In what way world religions can contribute to raise awareness and sense of responsibility.
Executive producer, Nasuhi Yurt.
Host : MaryLynn schiavi.
DVD format.
Keywords: Environmentalism; Environmental education